2021
DOI: 10.1007/s43615-021-00123-z
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Review Studies in Circular Economy: a Tertiary Study

Abstract: The importance of the circular economy has greatly increased in the past few years, and consequently, the interest in the circular economy as a research field has also increased, which led to an exponential growth in the number of literature reviews on the subject with different purposes. In order to analyze the topics that have been studied and assess the quality of these secondary reviews, this study carried out a tertiary literature review on the subject. This study identified the literature reviews on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 155 publications
0
3
0
2
Order By: Relevance
“…Ekonomi sirkular adalah topik yang menjadi penting dalam beberapa tahun terakhir, karena meningkatnya kelangkaan sumber daya alam dan perubahan perilaku konsumen. Ekonomi sirkular adalah sebuah model bisnis yang memaksimalkan implementasi strategi Reduce, Reuse, and Recycling (3R) terhadap sumber-sumber daya produksi (material, energi, dan air) yang digunakan pada fase proses produksi, distribusi, dan konsumsi (Barbosa, 2021). Penerapan ekonomi sirkular dapat membantu memecahkan masalah lingkungan yang timbul, seperti pengurangan waste semaksimal mungkin dan pengembalian waste atau sisa produksi ke siklus yang produktif sehingga mendorong sirkularitas sumber daya dalam sebuah proses produksi (Halog & Anieke, 2021).…”
Section: Circular Economy (Ekonomi Sirkular)unclassified
See 1 more Smart Citation
“…Ekonomi sirkular adalah topik yang menjadi penting dalam beberapa tahun terakhir, karena meningkatnya kelangkaan sumber daya alam dan perubahan perilaku konsumen. Ekonomi sirkular adalah sebuah model bisnis yang memaksimalkan implementasi strategi Reduce, Reuse, and Recycling (3R) terhadap sumber-sumber daya produksi (material, energi, dan air) yang digunakan pada fase proses produksi, distribusi, dan konsumsi (Barbosa, 2021). Penerapan ekonomi sirkular dapat membantu memecahkan masalah lingkungan yang timbul, seperti pengurangan waste semaksimal mungkin dan pengembalian waste atau sisa produksi ke siklus yang produktif sehingga mendorong sirkularitas sumber daya dalam sebuah proses produksi (Halog & Anieke, 2021).…”
Section: Circular Economy (Ekonomi Sirkular)unclassified
“…Implementasi ekonomi sirkular membawa beberapa manfaat bagi organisasi dan masyarakat, yaitu (Barbosa, 2021):…”
Section: Circular Economy (Ekonomi Sirkular)unclassified
“…As for the definition of the concept of CE, there are numerous suggestions [18]. Kirchherr et al [9] identified 114 definitions of the CE concept that emphasize different "Rs" (e.g., reduce, recycle, reuse). In this context, a popular definition of CE has been proposed by the Ellen MacArthur Foundation as "a restorative and a regenerative procedure which intends to retain final products, their parts, and waste materials into production processes every time" [36].…”
Section: A Conceptual Analysis Of the Circular Economy Term: A Triple...mentioning
confidence: 99%
“…The main goal of CE is to shift the focus of the current production system from the linear logic of "take, produce, consume and dispose" to "close the loop", where the end-of-life products return to the production stage and interventions are made throughout the technical or biological cycles of materials. A large part of the international literature has focused on CE's ability to contribute to sustainable development [9,10]. Particularly, studies have analyzed how and when the concept of CE is able to contribute to economic development, environmental preservation and social cohesion [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…1 because appropriate disposal and organization of MSW are prerequisites to reduce harmful ecological effects and degradation of surface and groundwater reserves. This is also advocated in a circular economy for long-term sustainability (e.g., [17,121,166]. Since, the definitive objective of a sustainable circular economy is global reductions in resource use and waste production [54,61].…”
Section: Introductionmentioning
confidence: 99%